The study group - Rogers, Kelly, 1981-; Peterschmidt, Betsy (Minneapolis, Minnesota Spellbound, 2017)
Neesha's friend Amy has been behaving very strangely since she joined Ms. Fleek's study group, ever so well behaved but remote--but Neesha misses her friend so much that she joins the group too, and immediately feels a change coming over her.
Neesha can wait -- Sleeping -- A rough week -- Welcome Neesha.
105121
Keywords: Science teachers -- Juvenile fiction; Middle schools -- Juvenile fiction; Horror stories; Teachers -- Fiction; Middle schools -- Fiction